Bahasa English Bahasa English - Moh Holilur Rohman (Istinbath : Jurnal Hukum, 2023)
A growing economy creates cryptocurrency virtual money residing in cyberspace. Cryptocurrency Is an online payment tool that uses an open source peer-to-peer payment network. There are many problems faced by users, where Cryptocurrencies are said to include money or a commodity. This phenomenon really makes users feel uncomfortable, feel at a loss, therefore the government must immediately provide an evaluation of the use of Cryptocurrency as a means of obtaining transactions. more attention, especially from the government so that the community gets their rights and obligations in muamalah. This paper aims to discuss how to use Cryptocurrency transactions from the Perspective of the DSN-MUI Fatwa and Law No. 7 of 2011. This research is classified as normative research, using a statutory approach and a conceptual approach. The results of the discussion show that Cryptocurrency is linked in the DSN MUI fatwa No.28/DSN-MUI/III/2002 regarding al-sharf that in the provisions of the fatwa the conditions for exchanging Cryptocurrency digital money are prohibited because of the element of speculation. In Article 2 paragraph (1) of Law Number 7 of 2011 concerning Cryptocurrency, it does not meet the requirements as a type of currency in Indonesia. Judging from the six criteria of money, Cryptocurrency only meets the criteria of portability and visibility.